RNA helicase Spn-E is required to maintain Aub and AGO3 protein levels for piRNA silencing in the germline of Drosophila. - Ryazansky, S.S.; Kotov, A.A.; Kibanov, M.V.; Akulenko, N.V.; Korbut, A.P.; Lavrov, S.A.; Gvozdev, V.A.; Olenina, L.V. (European Journal of Cell Biology, 2016)
Germline-specific RNA helicase Spindle-E (Spn-E) is known to be essential for piRNA silencing in Drosophila that takes place mainly in the perinuclear nuage granules. Loss-of-function spn-E mutations lead to tandem Stellate genes derepression in the testes and retrotransposon mobilization in the ovaries. However, Spn-E functions in the piRNA pathway are still obscure. Analysis of total library of short RNAs from the testes of spn-E heterozygous flies revealed the presence of abundant piRNA ping-pong pairs originating from Su(Ste) transcripts. The abundance of these ping-pong pairs were sharply reduced in the library from the testes of spn-E mutants. Thus we found that ping-pong mechanism contributed to Su(Ste) piRNA generation in the testes. The lack of Spn-E caused a significant drop of protein levels of key ping-pong participants, Aubergine (Aub) and AGO3 proteins of PIWI subfamily, in the germline of both males and females, but did not disrupt of their assembly in nuage granules. We found that observed decline of the protein expression was not caused by suppression of aub and ago3 transcription as well as total transcription, indicating possible contribution of Spn-E to post-transcriptional regulation.